Case report: Necrotising fasciitis after removing the intrauterine device - Özkaya, B.; Küçük, A.; Tosun, H.; GÜL, ASİYE (My University, 2018)
Necrotising fasciitis is a rapidly progressive, destructive soft tissue infection that mainly involves fascia and subcutaneous tissues. Rapidly spread necrosis in tissues is often caused by systemic sepsis, toxic shock syndrome, multiorgan failure and thrombosis in the subcutaneous vasculature. Necrotising fasciitis can be seen in all the anatomical regions of the body; the extremities and perineum are frequently affected. In this case report, we emphasised the importance of nursing care of a necrotising fasciitis patient who has been treated for a long time with aggressive surgical treatment. Vacuum-assisted closure application is a non-invasive method with controlled and localised negative pressure on the wound to accelerate healing in acute/chronic wounds. Necrotising fasciitis can be successfully treated with early diagnosis, adequate debridement, and appropriate antibiotic therapy. A multidisciplinary approach is necessary for the comprehensive care of these patients.
Keywords: Care; Necrotising Fasciitis; Vacuum-Assisted Closure; Wound; Bakım; Nekrotizan Fasiit; Vakum Destekli Kapatma; Yara